Role of calcitonin gene-related peptide in cerebral vasospasm, and as a therapeutic approach to subarachnoid hemorrhage - Kokkoris, Stelios; Andrews, Peter; Webb, David J. (Frontiers in Endocrinology, 2012)
Calcitonin gene-related peptide (CGRP) is one of the most potent microvascular vasodilators identified to date. Vascular relaxation and vasodilation is mediated via activation of the CGRP receptor. This atypical receptor is made up of a G-protein-coupled receptor called calcitonin receptor-like receptor (CLR), a single transmembrane protein called receptor activity-modifying protein (RAMP), and an additional protein that is required for Gas coupling, known as receptor component protein (RCP). Several mechanisms involved in CGRP mediated relaxation have been identified. These include nitric oxide (NO)-dependent endothelium-dependent mechanisms or cAMP-mediated endothelium-independent pathways; the latter being more common. Subarachnoid haemorrhage (SAH) is associated with cerebral vasoconstriction that occurs several days after the haemorrhage and is often fatal. The vasospasm occurs in 30–40% of patients and is the major cause of death from this condition. The vasoconstriction is associated with a decrease in CGRP levels in nerves and an increase in CGRP levels in draining blood, suggesting that CGRP is released from nerves to oppose the vasoconstriction. This evidence has led to the concept that exogenous CGRP may be beneficial in a condition that has proven hard to treat. The present article reviews: a) the pathophysiology of delayed ischaemic neurologic deficit after SAH b) the basics of the CGRP receptor structure, signal transduction and vasodilatation mechanisms and c) the studies that have been conducted so far using CGRP in both animals and humans with SAH.